The problematic definition of 'Chinese' in Hong Kong. (July 2019) - Clark, Adam Scott
Abstract: Hong Kong's language policy is codified in Article 9 of its Basic Law, which declares English and a non-specific 'Chinese' as the region's official languages. The definition of English is not particularly troublesome in Article 9; however, formulating a sound definition for the word 'Chinese' is problematic in the Hong Kong context. What does Chinese mean in Hong Kong? Does it refer to Cantonese, Putonghua, written Chinese, all of these or some of these? Hong Kong is a region wherein several languages are used with certain languages generally being used in specific domains and not in others. This situation is complex, far more so than Article 9 in its simplicity would lead us to believe. Using critical discursive methods, this article explores how Hong Kong's Basic Law is inadequate in properly dealing with Hong Kong's complex sociolinguistic situation and offers some suggestion as to how this might be remedied.